Respuesta :
-3x + 7y = 5x + 2y
-3(-5) + 7y = 5(-5) + 2y
15 + 7y = -25 + 2y
7y - 2y = -25 - 15
5y = -40
y = -40/5
y = -8
-3(-5) + 7y = 5(-5) + 2y
15 + 7y = -25 + 2y
7y - 2y = -25 - 15
5y = -40
y = -40/5
y = -8
Answer:
The missing value in the solution to the equation is -8.
Step-by-step explanation:
Here, the given equation,
-3x+7y = 5x+2y,
if x = -5,
-3(-5)+7y=5(-5)+2y,
15 + 7y = - 25+2y ( by solving brackets )
15 + 7y + 25 = 2y ( add 25 both sides )
40 + 7y = 2y
40 = 2y - 7y ( subtract 7 on both sides )
40 =-5y
⇒ y = -8 ( divide both sides by 5 )
Hence, the missing value in the solution to the equation is -8.